Altered apoptosis in bronchoalveolar lavage lymphocytes after allergen exposure of atopic asthmatic subjects - Muller, M; Grunewald, J; Olgart Hoglund, C; Dahlen, B; Eklund, A; Stridh, H (The European respiratory journal, 2006)
The increased number of lymphocytes in airways during an asthmatic response is believed to be the result of increased recruitment of these cells. However, it is possible that a decreased apoptotic rate could also contribute to the increased number. The aim of the present study was to investigate whether allergen airway provocation influences the apoptotic phenotype of lung and peripheral blood lymphocytes (PBL) in subjects with atopic asthma. Bronchoalveolar lavage (BAL) lymphocytes and PBL from 12 asthmatic subjects previously challenged with allergen (n = 7) or saline (n = 5) were exposed to the apoptotic stimulus tributyltin (TBT) in vitro and assayed for apoptosis. Airway allergen provocation resulted in decreased sensitivity of BAL lymphocytes to TBT-induced apoptosis, with 42.2% (range 33.9–62.5%) apoptotic cells before challenge versus 23.5% (range 15.3–42.4%) after challenge, while PBL were unaffected. The increased apoptosis resistance correlated with higher numbers of Bcl-2-expressing lymphocytes. Interestingly, baseline caspase-3-like activity was significantly elevated in viable BAL lymphocytes compared with viable PBL, and was unaltered by allergen exposure. In conclusion, allergen inhalation renders bronchoalveolar lavage lymphocytes more resistant to apoptosis while peripheral blood lymphocytes were not influenced at all, indicating that the apoptotic phenotype of airway lymphocytes may play a role in asthmatic inflammation.